penerapan penerapan seni baca al quran jenis mujawwad untuk meningkatkan kemampuan membaca al quran siswa sdn cileunyi 01: penerapan seni baca al quran jenis mujawwad untuk meningkatkan kemampuan membaca al quran siswa sdn cileunyi 01 - Lisa Ainul Jamil; Delis Sri Maryati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to identify the objective condition of students’ ability in reading the Qur’an, the implementation of the Mujawwad style of Qur’anic recitation in Islamic Education (PAI) learning, and the extent to which this method improves students’ reading skills in terms of tajwid and fluency (fashohah). This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results showed that the initial ability of fourth and fifth grade students was relatively low, as indicated by limited mastery of makharijul huruf, tajwid rules, and reading fluency. However, students demonstrated high interest and enthusiasm toward rhythm-based learning approaches. The implementation of the Mujawwad method was carried out in three main stages: strengthening the basic articulation of Arabic letters, teacher modeling, and student imitation practice. The findings revealed that approximately 50% of students showed improvement in their Qur’anic reading ability, particularly in pronunciation accuracy, basic tajwid comprehension, and reading fluency with proper rhythm. However, the improvement was not evenly distributed due to differences in students’ initial abilities, limited instructional time, and individual learning variations. Therefore, the Mujawwad method is considered effective in gradually improving students’ Qur’anic reading skills, although it requires continuous practice and intensive guidance